Early Prosthetic Valve Endocarditis Due to Finegoldia magna. (September 2019) - Cobo, Fernando; Calatrava, Elizabeth; Navarro-Marí, José María
Finegoldia magna is a Gram-positive anaerobic cocci frequently reported in human diseases. We report a rare case of mechanical prosthetic endocarditis due to this microorganism in a patient with heart disease. A 50-year-old man with prosthetic mitral and aortic valve presented with pericardial effusion, cardiac tamponade, and multiorgan dysfunction. Anaerobic blood cultures yielded a positive result, allowing further identification as F magna by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. The patient suffered replacement of mechanical mitral prosthesis by a new mechanical prosthesis, growing also F magna in the valvular culture. The isolate was identified as F magna by 16S ribosomal RNA sequence analysis. As a complication, a convulsive episode occurred, but a positive outcome was finally observed.